Nurses' knowledge and perception of delirium screening and assessment in the intensive care unit: Long-term effectiveness of an education-based knowledge translation intervention. (August 2017) - Hickin, Sharon L.; White, Sandra; Knopp-Sihota, Jennifer
Abstract: Objectives: To determine the impact of education on nurses' knowledge of delirium, knowledge and perception of a validated screening tool, and delirium screening in the ICU. Methods: A quasi-experimental single group pretest-post-test design. Setting: A 16 bed ICU in a Canadian urban tertiary care centre. Main outcome measures: Nursing knowledge and perception were measured at baseline, 3-month and 18-month periods. Delirium screening was then assessed over 24-months. Results: During the study period, 197 surveys were returned; 84 at baseline, 53 at 3-months post education, and 60 at the final assessment period 18-months post intervention. The significant improvements in mean knowledge scores at 3-months post intervention (7.2, SD 1.3) were not maintained at 18-months (5.3, SD 1.1). Screening tool perception scores remained unchanged. Improvements in the perception of utility were significant at both time periods ( p = 0.03, 0.02 respectively). Physician value significantly improved at 18-months ( p = 0.01). Delirium screening frequency improved after education ( p < 0.001) demonstrating a positive correlation over time ( p < 0.01). Conclusion: Multifaceted education is effective in improving delirium knowledge and screening; however, without sustained effort, progress is transient. Education improved perceived tool utility and over time utility perception and physician value improved.